Miss Independent : a simple 12-step plan to start investing and grow your own wealth - Lapin, Nicole (HarperCollins Leadership, 2022)
You've worked hard for your money and now it's time for your money to work for you. You will never earn or budget your way into real wealth. Growing your money significantly doesn't require starting with a lot of money. It requires a little bit of knowledge about taking smart risks and as much time as possible to take advantage of the glorious power of compound interest, which Einstein refers to as the eighth wonder of the world. From automating your savings to easy, no-stress investing strategies, Nicole will teach you how to take your financial knowledge and portfolio to the next level and start you on your journey to your ultimate destination: true financial independence.